Communication et santé : entre rationalité marchande, logique d'information et communauté d'intérêts - Annelise Touboul; Elizabeth Vercher (Tic & Société)
The Doctissimo group, which knows an impressive success in the fields of health and new technologies, was recently bought up by the giant Lagardere. Doctissimo.fr, its most important site, spreads medical information to the general public, popularizing knowledge previously restricted to health professionals. Its forums and others spaces for free expression are symptomatic of the general craze for these forms of communication known as participative and are symbolic of Web 2.0. This works tries to underline the operating way of the Doctissimo group and its site doctissimo.fr. It also wants to understand why these new forms of health mediations win the public support.